Socioeconomic and Environmental Determinants of Health Outcomes: The Case of Transition Economies - ÇAĞLAYAN AKAY, EBRU (POLITECHNIKA LUBELSKA, 2021)
This study examines the effects of economic and socio-demographic factors on the health status of men and women separately. The annual data of 16 selected transition countries for the period 2000-2016 were used. Life expectancy at birth was used as an indicator of health status in the study. Economic and environmental variables such as GDP per capita, health expenditures, unemployment, carbon emissions, access to safe water, and urbanization are considered as factors affecting life expectancy at birth. In the study, the Autoregressive Distributed Lags (ARDL) model was used. The findings show that the effects of socioeconomic and environmental factors on life expectancy differ according to men and women. It has been found that above-mentioned factors are more effective on life expectancy of men than women in selected transition economies. Therefore, it can be recommended to prioritize economic and environmental targets in improving the health outcomes of countries.
Keywords: Panel ARDL model; transition economies; health; socioeconomic factor; life expectancy; LIFE EXPECTANCY; EMPIRICAL-EVIDENCE; INCOME INEQUALITY; ADULT MORTALITY; PUBLIC-HEALTH; PANEL-DATA; UNEMPLOYMENT; EXPENDITURE; IMPACT; GENDER